If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2y(3y + -2) + -1y = -2(y + -4) Reorder the terms: -2y(-2 + 3y) + -1y = -2(y + -4) (-2 * -2y + 3y * -2y) + -1y = -2(y + -4) (4y + -6y2) + -1y = -2(y + -4) Reorder the terms: 4y + -1y + -6y2 = -2(y + -4) Combine like terms: 4y + -1y = 3y 3y + -6y2 = -2(y + -4) Reorder the terms: 3y + -6y2 = -2(-4 + y) 3y + -6y2 = (-4 * -2 + y * -2) 3y + -6y2 = (8 + -2y) Solving 3y + -6y2 = 8 + -2y Solving for variable 'y'. Reorder the terms: -8 + 3y + 2y + -6y2 = 8 + -2y + -8 + 2y Combine like terms: 3y + 2y = 5y -8 + 5y + -6y2 = 8 + -2y + -8 + 2y Reorder the terms: -8 + 5y + -6y2 = 8 + -8 + -2y + 2y Combine like terms: 8 + -8 = 0 -8 + 5y + -6y2 = 0 + -2y + 2y -8 + 5y + -6y2 = -2y + 2y Combine like terms: -2y + 2y = 0 -8 + 5y + -6y2 = 0 Begin completing the square. Divide all terms by -6 the coefficient of the squared term: Divide each side by '-6'. 1.333333333 + -0.8333333333y + y2 = 0 Move the constant term to the right: Add '-1.333333333' to each side of the equation. 1.333333333 + -0.8333333333y + -1.333333333 + y2 = 0 + -1.333333333 Reorder the terms: 1.333333333 + -1.333333333 + -0.8333333333y + y2 = 0 + -1.333333333 Combine like terms: 1.333333333 + -1.333333333 = 0.000000000 0.000000000 + -0.8333333333y + y2 = 0 + -1.333333333 -0.8333333333y + y2 = 0 + -1.333333333 Combine like terms: 0 + -1.333333333 = -1.333333333 -0.8333333333y + y2 = -1.333333333 The y term is -0.8333333333y. Take half its coefficient (-0.4166666667). Square it (0.1736111111) and add it to both sides. Add '0.1736111111' to each side of the equation. -0.8333333333y + 0.1736111111 + y2 = -1.333333333 + 0.1736111111 Reorder the terms: 0.1736111111 + -0.8333333333y + y2 = -1.333333333 + 0.1736111111 Combine like terms: -1.333333333 + 0.1736111111 = -1.1597222219 0.1736111111 + -0.8333333333y + y2 = -1.1597222219 Factor a perfect square on the left side: (y + -0.4166666667)(y + -0.4166666667) = -1.1597222219 Can't calculate square root of the right side. The solution to this equation could not be determined.
| -6x-3(x-4)=-51 | | 4(x+4)=16 | | 10=4x-5(x-4) | | 2x+2=24-2y | | an=0+(n-1)6 | | 6*(4y-10)=8*(2y-7) | | -70=-4x-5(-2x+8) | | (2/5)+y=3 | | 3a+20=2a+26 | | 6.8(x-2)=-0.2x+28.4 | | 187=3x+7(4x-3-3) | | 2x^2+x^2=400 | | 3(7x+5)=120 | | 4b=2b+24 | | 3x^2+46x+49=0 | | 7x-17=3x+9 | | 7(2+x)=42 | | 5x-17=3x+7 | | 6x-9x+5=x-2+7 | | 3x+5=7x | | 3x^2+x^2=100 | | 2(x-4)+3x=7 | | 3(2+4x)=6 | | 3x-8-7x=2x+8+2x | | 60(x+20)+3x=180 | | 8=2(4-3x)+6 | | y-8=(x-8) | | 60+20x+3x=180 | | 2x^2(x^2-3x+5)=0 | | 5(x+1)=-60 | | 24-3x=2x+4 | | (x-1)-3=0 |